Long-Term Risk-Sharing Wage Contracts in an Economy Subject to Permanent and Temporary Shocks - Gamber, Edward N. (Journal of Labor Economics, 1988)
This article develops and tests an implication of risk-shifting in labor market implicit contracts. A 2-period implicit contract model is presented. The optimal contract, in the face of bankruptcy constraints, calls for a real wage that responds asymmetrically to permanent and temporary shocks to the firm's revenue function. In particular, the real wage responds more to a permanent shock than to a temporary shock of the same size. This implication is tested on 12 4-digit Standard Industrial Classification (SIC) code industries. Eleven of the 12 industries sampled show evidence that supports the asymmetric wage response implication.